2022
DOI: 10.1136/lupus-2021-000611
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves renal injury of MRL/lpr lupus-prone mice via the AMPK/STAT3 pathway

Abstract: ObjectiveLupus nephritis (LN) is a major complication and cause of death among patients with SLE. This research used in vivo and in vitro experiments to explore the therapeutic potential of metformin in kidney injury from LN-induced inflammation.MethodsIn vivo study, 8-week-old MRL/MpJ-Faslpr/J (MRL/lpr) mice were randomly divided into two groups (n=12 each): daily administration of 0.3 mg/mL metformin in drinking water and control (water only). Body weight and urinary samples were measured biweekly. Mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Metformin Metformin can activate SIRT1 expression in macrophages, subsequently downregulating TLR4, p-NF-κB, IL-1β, and iNOS, and upregulating Arg1, and thereby inhibiting M1 macrophage polarization and promoting M2 polarization (Liu et al 2023). Chen et al also found that metformin can alleviate renal injury in patients with LN (Chen et al 2022b).…”
Section: Amino Acid Metabolismmentioning
confidence: 93%
“…Metformin Metformin can activate SIRT1 expression in macrophages, subsequently downregulating TLR4, p-NF-κB, IL-1β, and iNOS, and upregulating Arg1, and thereby inhibiting M1 macrophage polarization and promoting M2 polarization (Liu et al 2023). Chen et al also found that metformin can alleviate renal injury in patients with LN (Chen et al 2022b).…”
Section: Amino Acid Metabolismmentioning
confidence: 93%
“…Metformin ameliorates renal dysfunction in MRL/lpr lupus-prone mice, as proved by reductions in urinary protein and blood urea nitrogen levels. Furthermore, metformin decreases IgG and complement C3 deposition, and attenuates systemic and renal inflammation in this murine model ( 65 ). Metformin alleviates the autoimmune phenotype including kidney inflammation in lupus mice via restricting B cell transformation into plasma cells (PC) and germinal centers (GC) ( 66 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 97%
“…It decreased the proinflammatory cytokines and the levels of anti-nuclear antibody and anti-double stranded DNA antibodies. Metformin administration also attenuated histopathological damages (219). A post hoc analysis demonstrated that metformin decreased the incidence of flares in SLE patients, though patients with renal impairment were excluded (220).…”
Section: Antioxidantsmentioning
confidence: 99%